Construction of a recombinant vaccine expressing Nipah virus glycoprotein using the replicative and highly attenuated vaccinia virus strain LC16m8 - Watanabe, Shumpei; Yoshikawa, Tomoki; Kaku, Yoshihiro; Kurosu, Takeshi; Fukushi, Shuetsu; Sugimoto, Satoko; Nishisaka, Yuki; Fuji, Hikaru; Marsh, Glenn; Maeda, Ken; Ebihara, Hideki; Morikawa, Shigeru; et al. (PLoS neglected tropical diseases, 2023)
Nipah virus (NiV) is a highly pathogenic zoonotic virus that causes severe encephalitis and respiratory diseases and has a high mortality rate in humans (>40%). Epidemiological studies on various fruit bat species, which are natural reservoirs of the virus, have shown that NiV is widely distributed throughout Southeast Asia. Therefore, there is an urgent need to develop effective NiV vaccines. In this study, we generated recombinant vaccinia viruses expressing the NiV glycoprotein (G) or fusion (F) protein using the LC16m8 strain, and examined their antigenicity and ability to induce immunity. Neutralizing antibodies against NiV were successfully induced in hamsters inoculated with LC16m8 expressing NiV G or F, and the antibody titers were higher than those induced by other vaccinia virus vectors previously reported to prevent lethal NiV infection. These findings indicate that the LC16m8-based vaccine format has superior features as a proliferative vaccine compared with other poxvirus-based vaccines. Moreover, the data collected over the course of antibody elevation during three rounds of vaccination in hamsters provide an important basis for the clinical use of vaccinia virus-based vaccines against NiV disease. Trial Registration : NCT05398796 .